The characteristics of nitrogen and phosphorus output in China's highly urbanized Pearl River Delta region - Mao, Yupeng; Zhang, Hong; Cheng, Yuanhui; Zhao, Jianwei; Huang, Zhiwei (Journal of environmental management, 2023)
The nitrogen (N) and phosphorus (P) transportation due to the anthropogenic activities have strong correlations to the water pollution events. In the highly urbanized Pearl River Delta (PRD) region of China, the main input pathways for N and P have been changed. However, their main output pathways have not yet been understood. Based on the modified export coefficient model (ECM), we have quantified the N and P outputs and identified the main factors affecting the N and P outputs in highly urbanized areas such as PRD. The results showed that the N output intensity of the PRD has increased from 3010 to 3970 kg km−2·a−1 from 2008 to 2016. The P output exhibited a similar trend, from 549 to 769 kg km−2·a−1. In terms of spatial distribution, the output intensity gradually increased from economically underdeveloped regions to economically developed regions. N and P emissions in urban wastewater increased significantly with increasing urbanization rates, with output intensities increasing by 640 kg km−2·a−1 and 141 kg km−2·a−1 from 2008 to 2016, respectively. The correlation analysis showed that population density and urbanization rate were the most relevant factors with N and P outputs intensity in highly urbanized areas. This indicates that improving the effluent standards and utilization rates of wastewater treatment plants in these regions are effective measures to control N and P output. Our findings provide some new theoretical basis for the identification and management of pollution sources in highly urbanized areas for other regions, especially developing countries. •Urbanization and population affected N and P output.•Urban sewage contributed more pollution than agriculture.•Recommendations for regional pollution control are promoted.